Methane emissions from gathering pipeline networks, distribution systems, agriculture, waste management and natural sources - Pickering, Cody, author; Bradley, Thomas, advisor; Zimmerle, Daniel, advisor; Sheehan, John, committee member (Colorado State University. Libraries, 2016)
Climate change has influenced United States policymakers and industry professionals alike to minimize greenhouse gas emissions; including methane, the second most abundant greenhouse gas. The recent focus on quantifying methane emissions is not only motivated by its abundance but also the high global warming potential of the gas, which is 86 times greater than that of carbon dioxide on a 20-year timescale. Techniques to quantify methane emissions can be broken into three categories: component level, facility level, and basin level. In this study component level measurements and published emission estimates were used in Monte Carlo models to estimate regional methane emissions from three different source categories: natural gas gathering pipeline networks, natural gas distributions systems, and non-oil and gas sources such as: agriculture, waste management, lakes, ponds, rivers, wetlands and geological seepage. These estimates are designed to support a regional estimate including all methane sources for comparison against top-down emission estimates from aircraft measurements in the same region. Gathering pipeline networks are a sector of the natural gas supply chain for which little methane emissions data are available. In this study leak detection was performed on 96 kilometers of underground plastic pipeline and above-ground components including 56 pigging facilities and 39 block valves. Only one leak was located on an underground pipeline, however, it accounted for 83% of total measured emissions. Methane emissions estimated using a Monte-Carlo model for the 4684 km of gathering pipeline in the study area were 400 [+214%/-87%] kg/h (95% CI). This estimate is statistically similar to estimates based on emission factors from EPA’s 2015 Greenhouse Gas Reporting Program and is approximately 1% [0.1% to 3.2%] of the 39 Mg/h estimated in a prior aircraft measurement of the study region. The wide uncertainty range is due to two factors: one, the small sample size relative to the total gathering system in the study area and two, the presence of only one underground pipeline leak to characterize a range of possible emissions. The study also investigates what fraction of gathering pipelines in a basin must be measured to understand the maximum probable impact gathering line emissions could have on a basin level emission estimate. Distribution systems are a sector of the natural gas supply chain that has been analyzed and measured in recent years due to the attention they received in a 1992 study showing that they contribute approximately 25% of total methane emissions from the natural gas supply chain. The only distribution company in the study region provided data and access to their system for measurement during this study. During the field campaign, 129 of 239 metering and regulating stations were visited and 34 of 87 documented leaks from PHMSA surveys were visited. When scaling measured emissions to the eight counties in the study region, pneumatic emissions dominate, accounting for 2.8 [+37%/-31%] kg/h (95% CI) or 53% [42%-64%] of total emissions from measured sources. When including customer meters, the total distribution system in the 8 county study region contributes approximately 0.05% [0.02% to 0.12%] of the 39 Mg/h found in a prior aircraft measurement of the study region. While this study shows that the distribution system measurements are not a major contributor of emissions in this basin, it does not imply emissions are negligible on a national scale, since the rural regions in the study area had relatively little distribution infrastructure, and other distribution systems that may be older or constructed with materials that have higher leak rates, such as cast iron or unprotected steel. A detailed emission estimate from non-oil and gas sources was performed including poultry, cattle, swine, rice cultivation, landfills, wastewater treatment, wetlands, rivers, ponds and lakes, and geological seepage. This analysis supported emission estimates of previous work suggesting that cattle are the largest source of biogenic methane in this region. This analysis also indicates the importance of understanding geological seepage due to the large contribution that it may have to methane emissions from non-oil and gas sources. This analysis concludes that methane emissions from gathering pipeline networks, distributions systems, agricultural practices, waste management systems and natural sources contribute a small, but non-negligible, fraction of total methane emissions for this particular region which includes large-scale natural gas production. While methane emissions from the analyzed sources are proportionally low in the study region they are not necessarily proportionally small on a state, national or global scale.